2018
DOI: 10.1016/j.geomphys.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy circle and new fuzzy sphere through confining potentials and energy cutoffs

Abstract: Guided by ordinary quantum mechanics we introduce new fuzzy spheres S d Λ of dimensions d = 1, 2: we consider an ordinary quantum particle in D = d+1 dimensions subject to a rotation invariant potential well V (r) with a very sharp minimum on a sphere of unit radius. Imposing a sufficiently low energy cutoff to 'freeze' the radial excitations makes only a finite-dimensional Hilbert subspace accessible and on it the coordinates noncommutativeà la Snyder; in fact, on it they generate the whole algebra of observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(81 citation statements)
references
References 28 publications
3
78
0
Order By: Relevance
“…The decomposition of C Λ in irreducible representations of O(3) reads C Λ = 2Λ l=0 V l . In [1] we have shown that for all φ ∈ H s x i φ → (x i /r)φ ; more generally, settingf…”
Section: * -Automorphisms Of the Algebra Of Observablesmentioning
confidence: 93%
See 2 more Smart Citations
“…The decomposition of C Λ in irreducible representations of O(3) reads C Λ = 2Λ l=0 V l . In [1] we have shown that for all φ ∈ H s x i φ → (x i /r)φ ; more generally, settingf…”
Section: * -Automorphisms Of the Algebra Of Observablesmentioning
confidence: 93%
“…Here we present new fuzzy approximations [1] of quantum mechanics (QM) on S d (d = 1, 2) overcoming these two problems: We start with an ordinary zero-spin quantum particle in R D configuration space (D = d+1) with Hamiltonian…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covariant higher-dimensional fuzzy spaces were studied e.g. in [2,4,6,54,[88][89][90][91][92][93][94][95], which are similar in spirit to Snyder space [41,96], see also [47] for a somewhat related ansatz. In particular, the relation of fuzzy S 4 to fuzzy CP 2 was pointed out in [5,97,98], which is analogous to the bundle structure discussed in section 5.…”
Section: Further Literaturementioning
confidence: 99%
“…the angular momentum components L i map the generic V l into itself, while the x i map it into V l−1 ⊕ V l+1 . Moreover, relations (1) In [12] we have introduced some new fuzzy approximations of S 1 , S 2 -more precisely a fully O(2)-equivariant fuzzy circle {S 1 Λ } Λ∈N and a fully O(3)-equivariant fuzzy 2-sphere {S 2 Λ } Λ∈N ; the latter is free of the mentioned shortcomings. To construct S d Λ (d = 1, 2) we have first projected the Hilbert space L 2 (R D ) of a zero-spin quantum particle in R D (D := d+1) onto the finite-dimensional subspace H Λ spanned by all the ψ fulfilling…”
Section: Introductionmentioning
confidence: 99%